Pengaruh Model Pembelajaran Contextual Teaching Learning (CTL) Berbantuan Video Animasi Powtoon Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VII di MTsN 7 Tulungagung - Umi Nur Chofifah; Bagus Setiawan (Universitas 45 Surabaya, 2024)
This research is motivated by the value of learning outcomes of seventh grade students at MTsN 7 Tulungagung in social studies subjects that are still below KKM. The purpose of this research is to find out the influence and influence of the Contextual Teaching Learning (CTL) learning model aided by Powtoon-based animated videos on the results of social studies learning outcomes of VII grade students MTsN 7 Tulungagung, The method used in the study is a quantitative method of experimental type. Data collection techniques in this study using tests and documentation. The population is all VII grade students of MTsN Tulungagung totaling 302 students with a sample of 75 students selected by purposive sampling technique. Data were collected with 18 pretest questions and 19 posttest questions. The results of this study indicate that there is a significant effect on the application of the Contextual Teaching Learning (CTL) learning model on the social studies learning outcomes of seventh grade students at MTsN 7 Tulungagung with t count ≥ t table or 5.773 ≥ 1.666 and Sig. (2-tailed) 0.000 ≤ 0.05 at the 5% significance level, so it can be said that Ho is rejected and Ha is accepted. In addition, based on the effect size test, it is obtained that the influence of the Contextual Teaching Learning (CTL) learning model assisted by powtoon animation video on the learning outcomes of seventh grade social studies students at MTsN 7 Tulungagung is in the high category, namely 1.35 with a percentage of 90%.